EVALUASI STRATEGI BAD AN METEOROLOGI KLIMATOLOGI DAN GEOFISIKA - , Helmi Abadi; , Dr. Agus Setiawan, M.Soc.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Badan Meteorologi Klimatologi dan Geofisika (BMKG) is the only appointed by the government to provide information on meteorology, climatology, and geophysics in accordance with the provisions of applicable legislation. Therefore, the development of BMKG meteorology, climatology, air quality and geophysics do must be able to face the challenge of providing more information that has a strategic role in various aspects of civic life in various development sectors. Meteorology, climatology, air quality and geophysics development must be done in integrated, comprehensive implementation in accordance with the principles of integrity, equality, and commitment to be effective and efficient as mandated in No.30/2009 regulation about Meteorology, climatology, and geophysics. In implementing the service in the field of meteorology, climatology, air quality and geophysics, BMKG has provided information to stakeholder including: information services for aviation, shipping, environment, natural disaster or construction field. The main problem now is how the application BMKGâs business strategy as the only institution that provides services for Meteorology, climatology, air quality and geophysics in Indonesia in order to achieve goals and improve their performance. To obtain the answer, analyzing internal conditions is needed by analyzing the internal environment of human resources, budget, organization, and infrastructure. Then, external conditions analysis consists of goverment, demographic, sosial, natural, domestic, international, technology, and culture environment analysis should be done to obtain opportunities and threats that come from external environment. The results from these two analyses are used as input of SWOT analysis and internal-external matrix analysis. As a result, position of the company may revealed and based on those analysis company may decide, which strategy fit best by optimizing the ability to achieve company goals.. Based on space matrix analysis and internal-external matrix, BMKG has been identified having an advantageous situation, specifically on their potential power which can elaborate existing opportunities. The best strategy to perform is the strategy that encourages growth oriented strategy as already preformed by BMKG from 2005 thru 2010, which resulted in highest growth on 2009.